L’univers des anciens prisonniers politiques en Syrie - Yassin al-Haj Saleh (Revue des Mondes Musulmans et de la Méditerranée)
There were many political prisoners in Syria from the 1970s up to the early 1990s. In 1991 the state began a gradual release program which lasted until 2005. While prison life, interrogations and torture are sometimes discussed by ex-prisoners, their post-prison existence does not seem to arouse any interest in society. This article proposes to address that gap by analyzing the factors that weigh on post-prison life, including: the conditions for and the duration of imprisonment, the social and emotional environment encountered upon release, the re-establishment of social networks, the employability of ex-prisoners and available means of subsistence – so many elements necessary for successful reintegration. Political prisoners face significant difficulties upon release, including the need to rehabilitate their own images. Some efforts are currently under way to assist with rehabilitation and compensation for these unjustly destroyed individuals.